(untitled) (Colombia Medica, 2010)
Schizophyllum commune is a basidiomycete fungus with broad distribution in nature; however, it is a rare cause of infectious disease. We report the isolation of this mould in a 46 year-old immunocompetent patient with chronic sinusitis previously treated with multiple antibiotics and topical nasal steroids. Material obtained via a left maxillary sinus antrostomy showed septate hyaline hyphae with clamp connections on direct examination with KOH and histopathological studies. Further growth on Sabouraud agar produced a white mould that, based on its microscopic and macroscopic characteristics, was identified as S. commune. Despite its low frequency, this fungus should be considered a possible pathogen, particularly in samples obtained from paranasal sinuses.